2008
DOI: 10.1016/s0929-6646(08)60156-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combining Ultralow-dose Naloxone with Morphine in Intravenous Patient-controlled Analgesia: The Cut-off Ratio of Naloxone to Morphine for Antiemesis After Gynecologic Surgery

Abstract: The antiemetic efficacy of ultralow-dose naloxone combined with PCA morphine is limited by a cut-off ratio of naloxone to morphine of 1:10,000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…1416 Although the use of a continuous basal opioid infusion is not universal in pediatric pain management, it is more frequently used 2,14,17 than in adult practice. 1,8,9,12,16 Our findings that a higher naloxone infusion rate more effectively reduced pruritus in children receiving basal/bolus IV PCA than the lower doses reported to be effective in adult patients receiving bolus-only PCA are similar to those reported in a small pilot study of patients with sickle cell anemia who received morphine via continuous infusion in combination with naloxone. 18 …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…1416 Although the use of a continuous basal opioid infusion is not universal in pediatric pain management, it is more frequently used 2,14,17 than in adult practice. 1,8,9,12,16 Our findings that a higher naloxone infusion rate more effectively reduced pruritus in children receiving basal/bolus IV PCA than the lower doses reported to be effective in adult patients receiving bolus-only PCA are similar to those reported in a small pilot study of patients with sickle cell anemia who received morphine via continuous infusion in combination with naloxone. 18 …”
Section: Discussionsupporting
confidence: 82%
“…8,9,12 Although we also found side effect amelioration at lower doses in our study, higher doses (≥1 µg/kg/h) were more consistently effective. A possible explanation for these different results may simply be related to how IV PCA was provided in this study.…”
Section: Discussionsupporting
confidence: 52%
“…Three of nine studies recorded postoperative antiemetic medication doses and found statistically significant decreases among patients receiving naloxone (RR 0.64 #bib95% CI 0.42–0.96, p=0.03; Figure ) . However, reduction in antiemetic dosing needs and PONV among patients receiving naloxone should be interpreted with caution based on limited patient documentation (n=186) relative to the total patient pool (n=946).…”
Section: Resultsmentioning
confidence: 99%
“…11 Studies of naloxone-opioid PCA admixtures in adult patients have reported varying results, including poorer quality of analgesia, 12 no benefit, 13 or improved side effects with unchanged pain and opioid requirements. 14,15 Clearly, reducing adverse effects without compromising the quality of analgesia or increasing opioid consumption requires careful selection of the relative doses of naloxone and morphine. A dose-finding study in children showed that naloxone 1 lgÁkg -1 Áhr -1 was the minimum dose at which participants were successfully treated for OIP with a \ 10% failure rate and that 1.65 lgÁkg -1 Áhr -1 was as effective without increasing opioid requirements.…”
Section: Résumémentioning
confidence: 99%